1983
DOI: 10.1021/bk-1983-0223.ch008
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Adsorption Processes: State of the Art

Abstract: Gas-adsorption processes are used for a wide variety of separations throughout the chemical and other industries. But to effect various separations, quite different process embodiments are necessary. These differences are primarily concerned with the method by which the adsorbent is regenerated. This choice is influenced by the percentage of adsorbate in the feed, ease of desorption and degree of separation required. In this paper, we discuss temperature-swing, inert-purge, displacement-purge, pressure-swing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…This research dealt with bulk separation [separation of gases containing over 10% by weight of adsorbate according to Keller's (1983) definition] where strongly-and weakly-adsorbed components were both wanted products. Fifteen experiments were performed to separate a feed mixture of 50/50 (by volume) Hz and C H I into two high-concentration products.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This research dealt with bulk separation [separation of gases containing over 10% by weight of adsorbate according to Keller's (1983) definition] where strongly-and weakly-adsorbed components were both wanted products. Fifteen experiments were performed to separate a feed mixture of 50/50 (by volume) Hz and C H I into two high-concentration products.…”
Section: Resultsmentioning
confidence: 99%
“…PSA has attracted increasing interest more recently because of its low energy requirements as well as low capital investment costs (Stewart and Heck, 1969). State-of-the-art reviews of the PSA processes may be found in Keller (1983), Cassidy and Holmes (1984), and Wankat (1981). In modern PSA processes, three or more beds are used to synchronize and accommodate two additional steps to those in the Skarstrom cycle: cocurrent depressurization and pressure equalization.…”
Section: Conclusion and Significancementioning
confidence: 99%
See 2 more Smart Citations
“…The advent of commercial PSA operations started with the early patents but its first application was offered later 20 . Since then, PSA has become the state-of-the-art separation technology for large variety of applications like air fractionation and hydrogen production [21][22][23][24] . The PSA processes are much more efficient in separation and are also associated to low energy consumption when compared to other technologies because only stepped changes in pressure are required 25 .…”
Section: Introductionmentioning
confidence: 99%